Downregulation of P2Y12 in the superior cervical ganglia alleviates abnormal sympathetic activity after myocardial ischemia. Issue 4 (1st November 2017) - Zou, Lifang; Gong, Yingxin; Zhao, Shanhong; Yi, Zhihua; Han, Xinyao; Wu, Bing; Jia, Tianyu; Li, Lin; Yuan, Huilong; Shi, Liran; Zhang, Chunping; Gao, Yun; et al.
Abstract : Superior cervical ganglia (SCG) innervate the myocardium and participate in sympathoexcitatory transmission. P2Y12 receptor is expressed in satellite glial cells (SGCs). This study seeks to clarify whether the P2Y12 receptor is involved in the sympathoexcitation reflex after myocardial ischemia (MI). MI model was induced by occlusion of the left coronary artery. P2Y12 were assayed by real time PCR and Western blotting. Our results showed that expression levels of P2Y12 mRNA and protein were significantly higher in the MI group than in the sham group. Administration of P2Y12 short hairpin RNA (shRNA) caused downregulation of the P2Y12 receptor in the SCG. In MI rats plus P2Y12 shRNA treatment group, the abnormal changes in diastolic blood pressure (DBP), systolic blood pressure (SBP), heart rate (HR), electrocardiograms (ECGs), and cardiac tissue structures were alleviated. When the treatment of P2Y12 shRNA in MI rats, upregulated co‐expression values of P2Y12 and glial fibrillary acidic protein (GFAP), the upregulation of tumor necrosis factor α (TNF‐α) and phosphorylated P38 mitogen activated protein kinase (p‐P38 MAPK) in the SCG were decreased. Downregulation of the P2Y12 receptor in the SCG after MI may improve cardiac function by alleviating the sympathoexcitatory reflex. Abstract : Superior cervical ganglia (SCG) innervate the myocardium and participate in sympathoexcitatory transmission. P2Y12 receptor is expressed in satellite glial cells (SGCs). Downregulation of the P2Y12 receptor in the SCG after myocardial ischemia may improve cardiac function by alleviating the sympathoexcitatory reflex.